A role of CD20+ T cells in early multiple sclerosis - von Essen, Marina Rode; Hansen, Marie Mathilde; El Mahdaoui, Sahla; Hvalkof, Victoria Hyslop; Hansen, Rikke Holm; Nielsen, Jørgen E.; Frederiksen, Jette; Sellebjerg, Finn (Frontiers in Immunology, 2025)
Relapsing-remitting multiple sclerosis (RRMS) is a chronic immune-mediated disease of the central nervous system (CNS) characterized by episodic relapses of neurological symptoms. Early diagnosis and treatment of patients is key to prevent relapses and irreversible damage to the CNS. However, development of therapies targeting early MS is constrained by the lack of knowledge of early MS disease pathogenesis. In RRMS, nervous tissue damage is induced by CNS-infiltrating immune cells, including T cells. The aim of this study was therefore to investigate the early events of CNS infiltration by T cells in RRMS, including their interaction with astrocytes and brain endothelial cells. Using a human in vitro model system and tissue samples obtained from newly diagnosed patients and healthy individuals, we found that CD8+CD20+ T cells could cross the blood-brain-barrier (BBB) and blood-cerebrospinal fluid-barrier in the absence of inflammation. As CD8+CD20+ T cells are present in the CNS before inflammation and are highly enriched in MS lesions once the disease is initiated, they may be among the first effector cells in RRMS. Our study also showed that CD4+CD20+ T cells can stimulate brain endothelial cells to express adhesion molecules and chemokines needed for peripheral immune cells to adhere and migrate through the BBB, and stimulate astrocytes to produce chemokines directing transmigrating cells to the site of inflammation. This suggests that CD4+CD20+ T cells, once migrated to the CNS, strengthens the infiltration of immune cells to the CNS and hereby amplify CNS inflammation. Altogether, this indicates that CD20+ T cells play a role in the early phases of MS-inflammation and therefore are candidate targets for early treatment.